Experimental Investigation into the Production Behavior of Methane Hydrate in Porous Sediment by Depressurization with a Novel Three-Dimensional Cubic Hydrate Simulator - Li, Xiao-Sen; Zhang, Yu; Li, Gang; Chen, Zhao-Yang; Wu, Hui-Jie (Energy & Fuels, 2011)
The gas production behavior from methane hydrate in a porous sediment by depressurization was investigated in a three-dimensional (3D) cubic hydrate simulator (CHS) at 281.15 K, hydrate saturation of 33.1%, and a production pressure range of 4.5-5.6 MPa. The results show that the gas production process consists of three periods: free gas production, mixed gas (free gas and gas dissociated from the hydrate) production, and gas production from the hydrate dissociation. The temperature in the near-well region in the 3D hydrate reservoir changes during gas production in five stages. In the first period, the free gas in the system is released and the temperature change is not significant. In the second period, the temperature increases because of the reformation of the hydrate. In the third period, the temperature at each measuring point decreases quickly to the lowest value because of the considerable dissociation of the hydrate. The fourth period is the thermostatic hydrate dissociation period. During this period, the temperature at each point remains constant. In the fifth period, the hydrate has almost dissociated completely and the temperatures gradually increase to the environmental temperature of 281.15 K. There is no thermostatic dissociation period in the far-from-well region, in which the temperature at each measuring point gradually increases after it reaches the lowest value. In the third period of gas production, the temperatures in the near-well region are lower than those in the far-from-well region. In the gas production process, the resistances in the hydrate reservoir change with the hydrate dissociation and the flow of the gas and water. It can also be found that the gas production rate and the cumulative gas production increase with the decrease of the pressure. The gas hydrate dissociation in the gas production process is mainly controlled by the rate of the pressure reduction in the system and the heat supplied from the ambient. There is significant water production in the free gas production ...